Profil Klinikopatologik Kasus Adenokarsinoma Prostat di RSCM Tahun 2010-2019 dengan Tinjauan Khusus Biopsi Robotik - Rizky Prasetya, Gusti; Saraswati, Meilania; Rizal AH. Hamid, Agus; BRE. Matondang, Sahat (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2022)
BackgroundProstate adenocarcinoma is second most common malignancy in men and fourth leading death cause from malignancy worldwide. Prostate biopsy is the gold standard for diagnosing this disease. However, the difficulty of sampling is a weakness in this procedure. In Cipto Mangunkusumo hospital, biopsy technology is now available with robotic techniques for biopsy sampling, which is expected to increase prostate biopsy accuracy. This study was to determine prostate adenocarcinoma case profile in the Department of Pathology Anatomic Cipto Mangunkusumo Hospital for 10 years and to examine differences in sampling of biopsy preparations with robotic and non-robotic techniques. MethodsThis study was an exploratory descriptive study with cross-sectional design to determine prostate adenocarcinoma case profile in the Department of Anatomic Pathology FKUI-RSCM for 10 years. The data obtained between the Gleason score of prostate biopsy preparations and surgery. Robotic prostate biopsy results were compared with prostate imaging reporting and data system (PIRADS) score. ResultsThe mean age of the patients was 67 years old and several patients were aged <50 years old. Many poor differentiation cases were found. It appears that there is a relationship between WHO/ISUP degree and perineural invasion. In 14 patients who underwent histopathological examination more than once, it was found that 9 patients had the same WHO/ISUP degree and 5 patients had a changed WHO/ISUP degree. There are several discrepancies in PIRADS score and histopathological findings from 21 robotic preparations examined. ConclusionThe mean age of patients fit to theory of generalized prostate adenocarcinoma. Many cases of poor differentiation were found, possibly related to RSCM as a national referral center. The repeated sample examination results are similar to the results of other studies. Robotic method biopsy gives the sense of more comprehensive sampling in comparison to non-robotic method.